Pathophysiology, clinical presentation, and treatment of coma and acute kidney injury complicating falciparum malaria - Plewes, K; Turner, G; Dondorp, A (Lippincott, Williams & Wilkins, 2018)
Cerebral impairment and acute kidney injury (AKI) are independent predictors of mortality in both adults and children with severe falciparum malaria. In this review, we present recent advances in understanding the pathophysiology, clinical features, and management of these complications of severe malaria, and discuss future areas of research.Cerebral malaria and AKI are serious and well recognized complications of severe malaria. Common pathophysiological pathways include impaired microcirculation, due to sequestration of parasitized erythrocytes, systemic inflammatory responses, and endothelial activation. Recent MRI studies show significant brain swelling in both adults and children with evidence of posterior reversible encephalopathy syndrome-like syndrome although targeted interventions including mannitol and dexamethasone are not beneficial. Recent work shows association of cell-free hemoglobin oxidation stress involved in the pathophysiology of AKI in both adults and children. Paracetamol protected renal function likely by inhibiting cell-free-mediated oxidative stress. It is unclear if heme-mediated endothelial activation or oxidative stress is involved in cerebral malaria.The direct causes of cerebral and kidney dysfunction remain incompletely understood. Optimal treatment involves prompt diagnosis and effective antimalarial treatment with artesunate. Renal replacement therapy reduces mortality in AKI but delayed diagnosis is an issue.